How Change Happens - Green, Duncan (OUP Oxford, 2016)
Human society is full of would-be 'change agents', a restless mix of campaigners, lobbyists, and officials, both individuals and organizations, set on transforming the world. They want to improve public services, reform laws and regulations, guarantee human rights, get a fairer deal for those on the sharp end, achieve greater recognition for any number of issues, or simply be treated with respect. Striking then, that not many universities have a Department of Change Studies, to which social activists can turn for advice and inspiration. Instead, scholarly discussions of change are fragmented with few conversations crossing disciplinary boundaries, rarely making it onto the radars of those actively seeking change. This book bridges the gap between academia and practice, bringing together the best research from a range of academic disciplines and the evolving practical understanding of activists to explore the topic of social and political change. Drawing on many first-hand examples from the global experience of Oxfam, one of the world's largest social justice NGOs, as well as the author's insights from studying and working on international development, it tests ideas on How Change Happens and offers the latest thinking on what works to achieve progressive change. This is an open access title available under the terms of a CC BY-NC-ND 4.0 International licence. It is available as a free PDF download from OUP and selected open access locations.

Governance and Service Delivery: Practical Applications of Social Accountability Across Sectors - Wetterberg, Anna; Brinkerhoff, Derick W.; Hertz, Jana C. (RTI Press, 2016)
The six case studies in Governance and Service Delivery: Practical Applications of Social Accountability Across Sectors illustrate the multiple ways citizen participation in accountability – called social accountability – can lead to positive effects on governance, citizen empowerment, and service delivery. Drawing on their extensive experience implementing international donor-funded programs and projects, the authors examine six recent RTI International projects in Africa and Asia. The analysis focuses on both intended and actual effects, and it unpacks the influence of context on implementation and outcomes achieved, as well as on prospects for sustainability. Donors, academics, policy makers, practitioners and others interested in sustainable development and governance will find this systematic review invaluable.

How China Escaped the Poverty Trap - Ang, Yuen Yuen (Cornell University Press, 2016)
Before markets opened in 1978, China was an impoverished planned economy governed by a Maoist bureaucracy. In just three decades it evolved into the world's second-largest economy and is today guided by highly entrepreneurial bureaucrats. In How China Escaped the Poverty Trap, Yuen Yuen Ang explains this astonishing metamorphosis. Rather than insist that either strong institutions of good governance foster markets or that growth enables good governance, Ang lays out a new, dynamic framework for understanding development broadly. Successful development, she contends, is a coevolutionary process in which markets and governments mutually adapt.By mapping this coevolution, Ang reveals a startling conclusion: poor and weak countries can escape the poverty trap by first harnessing weak institutions―features that defy norms of good governance―to build markets. Further, she stresses that adaptive processes, though essential for development, do not automatically occur. Highlighting three universal roadblocks to adaptation, Ang identifies how Chinese reformers crafted enabling conditions for effective improvisation.How China Escaped the Poverty Trap offers the most complete synthesis to date of the numerous interacting forces that have shaped China’s dramatic makeover and the problems it faces today. Looking beyond China, Ang also traces the coevolutionary sequence of development in late medieval Europe, antebellum United States, and contemporary Nigeria, and finds surprising parallels among these otherwise disparate cases. Indispensable to all who care about development, this groundbreaking book challenges the convention of linear thinking and points to an alternative path out of poverty traps.
Keywords: IMPORTANT

The Scrum Guide - Schwaber, Ken; Sutherland, Jeff (scrum.org, 2016)

Christian Practical Wisdom: What It Is, Why It Matters - Bass, Dorothy C.; Cahalan, Kathleen A.; McLemore, Bonnie J.; Nieman, James R.; Scharen, Christian B. (Wm. B. Eerdmans Publishing Company, 2016)
Why is the very kind of knowledge that people need to live well ― practical wisdom ― often the least understood, the hardest to learn, and the most devalued kind of knowledge?In this book five distinguished practical theologians examine the wisdom that is basic for faithful Christian living, question why it has been largely devalued, and advocate for its renewal. After first showing several concrete situations in which this kind of wisdom is visible ― marriage, church, community, culture, and more ― the authors then delve into the reasons for the decline of practical wisdom and set forth constructive cases for its renewal through biblical imagination and spiritual practice.

Designing Regenerative Cultures - Wahl, Daniel Christian (Triarchy Press Ltd, 2016)
This is a 'Whole Earth Catalog' for the 21st century: an impressive and wide-ranging analysis of what's wrong with our societies, organizations, ideologies, worldviews and cultures - and how to put them right. The book covers the finance system, agriculture, design, ecology, economy, sustainability, organizations and society at large. In this remarkable book, Daniel Wahl explores ways in which we can reframe and understand the crises that we currently face, and he explores how we can live our way into the future. Moving from patterns of thinking and believing to our practice of education, design and community living, he systematically shows how we can stop chasing the mirage of certainty and control in a complex and unpredictable world. The book asks how can we collaborate in the creation of diverse regenerative cultures adapted to the unique biocultural conditions of place? How can we create conditions conducive to life? *** "This book is a valuable contribution to the important discussion of the worldview and value system we need to redesign our businesses, economies, and technologies - in fact, our entire culture - so as to make them regenerative rather than destructive." --Fritjof Capra, author of The Web of Life, co-author of The Systems View of Life: A Unifying Vision *** "This is an excellent addition to the literature on ecological design and it will certainly form a keystone in the foundations of the new MA in Ecological Design Thinking at Schumacher College, Devon. It not only contains a wealth of ideas on what Dr Wahl has termed 'Designing Regenerative Cultures' but what is probably more important, it provides some stimulating new ways of looking at persistent problems in our contemporary culture and hence opens up new ways of thinking and acting in the future." -- Seaton Baxter OBE, Prof. in Ecological Design Thinking, Schumacher College, UK [Subject: Systems Thinking, Education, Social Anthropology, Environmentalism, Ecology, Regenerative Culture, Sociology]

Digital Technologies for Democratic Governance in Latin America: Opportunities and Risks - Breuer, Anita; Welp, Yanina (Routledge, 2016)
This book is the first to comprehensively analyse the political and societal impacts of new Information and Communication Technologies (ICT) in a region of the Global South. It evaluates under what conditions some Latin American governments and people have succeeded in taking up the opportunities related to the spread of ICTs, while others are confronted with the pessimist scenario of increased, digitally induced social and democratic cleavages. Specifically, the book examines if and how far the spread and use of new ICT affected central aims of democratic governance such as reducing socio-economic and gender inequality; strengthening citizen participation in political decision making; increasing the transparency of legislative processes; improving administrative processes; providing free access to government data and information; and expanding independent spaces of citizen communication. The country case and cross-country explore a range of bottom-up driven initiatives to reinforce democracy in the region. The book offers researchers and students an interdisciplinary approach to these issues by linking it to established theories of media and politics, political communication, political participation, and governance. Giving voice to researchers native to the region and with direct experience of the region, it uniquely brings together contributions from political scientists, researchers in communication studies and area studies specialists who have a solid record in political activism and international development co-operation.

Simple Habits for Complex Times: Powerful Practices for Leaders - Berger, Jennifer Garvey; Johnston, Keith (Stanford University Press, 2016)

Innovation for International Development: Navigating the Paths and Pitfalls - Ramalingam, Ben; Bound, Kirsten (NESTA, 2016)
Experiences, insights and practical advice from over 20 leading practitioners in innovation for international development, brought together in one collection.

The MSP Tool Guide: Sixty tools to facilitate Multi-Stakeholder Partnerships - Brouwer, Herman; Brouwers, Jan (CDI, Wageningen University and Research, 2016)
What is ‘The MSP Tool Guide’ all about? This compilation of 60 tools is an companion to The MSP Guide, the Wageningen University & Research CDI resource on how to design and facilitate effective multi-stakeholder partnerships. At the request of many readers we have compiled them into one document to enable easy storing and sharing. These tools are available in summarized version in the MSP Guide in Chapter 6. The detailed versions on how to use the tool, and when to use it, are available on the portal www.mspguide.org/tools-and-methods. The content of this portal is compiled in this Tool Guide.

The MSP Guide: How to Design and Facilitate Multi-Stakeholder Partnerships - Brouwer, Herman; Woodhill, Jim; Hemmati, Minu; Verhoosel, Karèn; van Vugt, Simone (Practical Action Publishing, 2016)
In recent years, multi-stakeholder partnerships (MSPs) have become popular for tackling the complex challenges of sustainable development. This guide provides a practical framework for the design and facilitation of these collaborative processes that work across the boundaries of business, government, civil society and science. The guide links the underlying rationale for multistakeholder partnerships, with a clear four phase process model, a set of seven core principles, key ideas for facilitation and 60 participatory tools for analysis, planning and decision making. The guide has been written for those directly involved in MSPs – as a stakeholder, leader, facilitator or funder – to provide both the conceptual foundations and practical tools that underpin successful partnerships. What’s inside draws on the direct experience of staff from the Wageningen Centre of Development Innovation (WCDI), at Wageningen University & Research, in supporting MSP processes in many countries around the world. The guide also compiles the ideas and materials behind WCDI’s annual three week international course on facilitating MSPs and social learning. This work has been inspired by the motivation and passion that comes when people dare to “walk in each other’s shoes” to find new paths toward shared ambitions for the future.

Monitoreo ciudadano en México: Participación ciudadana para mejorar la provisión de servicios públicos - Hevia, Felipe (CIDE, 2016)
Existe un amplio consenso sobre la importancia de los sistemas de monitoreo y evaluación para la mejora de políticas, programas y servicios públicos. Sin embargo, en la literatura especializada sorprende el escaso interés por analizar un tipo